National identity as a path towards the compatibility of the opposite standpoints - Griciūnas, Paulius (Vilnius University Open Series, 2020)
Both the unconditional primacy of the EU law (even over all the national constitutional norms), and the supremacy of any national constitutional rule over EU law, couldn’t be considered as a solution to the accommodation of the constructive interaction between two autonomous legal systems. The pluralistic models come up with a solid explanation on how legal systems interact. However, they fail to provide a solution when it comes to the potential collision of the EU and national constitutional norms. In the last decade, discourse on the notion of national identity has been developing. This concept could be a viable approach in resolving situations (as researched in this article2) bordering on conflict in the pluralistic models.